2014
DOI: 10.46429/jaupr.v98i1.217
|View full text |Cite
|
Sign up to set email alerts
|

Yield performance of eight snap bean genotypes grown under an organic management system in the tropics

Abstract: Eight snap bean (Phaseolus vulgaris L.) cultivars and lines were grown under an organic management system in 2011 and 2012 in Lajas, Puerto Rico. Bean genotypes used in the trial were the commercial cultivars 'Contender', 'Festina', 'Fresh Pick', 'Jade', 'Nash' and 'Provider', and two experimental breeding lines PR1018-1 and PR1018-5. In 2011, 'Provider' and PR1018-5had the highest yields, with 11.2 and 11.1 t/ha, respectively, but these were not significantly different from the yields of 'Contender', 'Festina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…The variance between cultivars can be explained on the basis that, yield and quality of snap bean are affected by genotype of the variety (Nassar, 1986 andAmer et al, 2002). The same results were reported by Abdel-Mawgoud et al (2005) and Brunner et al (2014).…”
Section: -supporting
confidence: 91%
“…The variance between cultivars can be explained on the basis that, yield and quality of snap bean are affected by genotype of the variety (Nassar, 1986 andAmer et al, 2002). The same results were reported by Abdel-Mawgoud et al (2005) and Brunner et al (2014).…”
Section: -supporting
confidence: 91%
“…Napoli cultivar was among the least productive in both systems. Higher yield values found in the conventional cultivation system are in agreement with Brunner et al (2014), who found, in na organic system in Puerto Rico, Panama, yields of marketable pods superior to those found in conventional system. They also agree with Portal et al (2018), who, studying genotypes of wild bean of indeterminate growth, in the same place, also found better yield performance in organic production system.…”
Section: /6supporting
confidence: 90%
“…In a study with the production components of bush snap beans, in conventional and organic systems, Gomes et al (2017) observed that the cycle was shorter in the conventional system and that there was interaction between cultivars and cultivation systems, with the plants having greater development in the organic system, without affecting the yield of marketable pods. Brunner et al (2014), studied eight snap bean cultivars in an organic system and observed yield results ranging from 9.9 to 14.6 tons of pods per hectare.…”
Section: Introductionmentioning
confidence: 99%
“…Vaz et al (2017) studied 29 bush snap bean genotypes, from different countries of origin, under conventional cultivation, in Ipameri-GO, of which 19 are from the same study, and recorded the cultivars Contender, Jade, and Provider as the most productive (18 t ha -1 ). Brunner et al (2014) analyzed eight bush snap bean genotypes, in an organic system, in Puerto Rico and found that the cultivars Provider, Contender, Festina, and Jade were among the most productive, with a range from 10.90 to 14.60 t ha -1 . Andrade et al (2017) evaluated 25 bush snap bean accessions under organic cultivation in Londrina-PR; they found yields between 5.14 and 9.72 in the September-December season and between 7.02 and 11.07 t ha -1 in April-June.…”
Section: Resultsmentioning
confidence: 99%